Construction and validation of an educational video on laboratory test collection errors (Revista Contexto & Saúde, 2023)
Clinical analysis exams help in the diagnosis of diseases and when it presents inaccurate results it can impair medical conduct. This work aims to produce and validate an educational video about situations involving pre-analytical errors in a clinical analysis laboratory. The methodological study consisted of three stages: 1) production of a script and preliminary video; 2) validation of the video by experts; 3) final production, recording and editing of the educational video. For data collection, we used a collection instrument composed of ten statements that dealt with the situations addressed in the video, as well as their clarity and performance of the actors, followed by a Likert-type scale with four items: Totally Agree, Agree, Disagree and Strongly Disagree, as well as an open question so that each judge could register their impressions and suggestions about each scene in the video. The analysis of this instrument was performed by calculating the concordance index (CI). Items with CI ≥ 70% were considered valid. Validation was performed by experts and two video scenes showed CI ≤ 70%. It was necessary to adjust these scenes as suggested by the judges. A new preliminary version of the video was produced, undergoing a new validation stage and all items presented a CI ≥ 70%. The video on laboratory test collection errors was validated by expert judges in the field of clinical analysis and communication, who considered the video adequate to promote learning on the subject.
Keywords: pre-analytical phase; clinical laboratory techniques; educational films and videos